Is Pilates a Somatic Education Method? - Bolsanello (Université du Québec à Montréal, Montreal, Canada) Débora Pereira (Revista Brasileira de Estudos da Presença, 2022)
This paper renews the discussion about the relevance of the Pilates method to the field of Somatic Education. The impact of marketing – which sells the method as a fitness activity – and the academic research on the application of the method in the treatment of various medical disorders, as well as its role in the construction of contemporary dance aesthetics, are put into perspective.